Programa de cuidado psicológico e habilidades socioemocionais para adolescentes de Ensino Médio: uma perspectiva da psicologia analítica - Vasconcellos, Ana Paula Navarro de (2024)
This research aimed to investigate the effectiveness of a psychological care and socioemotional skills development program for high school adolescents in public schools. The verification hypotheses considered the increase in the repertoire of skills and the decrease in reported emotional and behavioral problems. This is a mixed-method quasi-experimental study with pre/post-test/follow-up, experimental group (EG), and control group (CG), grounded in the Jungian psychology theoretical framework. Sixty-four second-year high school students aged between 16 and 18 years from two schools in São Bernardo do Campo/SP participated (EG/n=30; CG/n=34). The program consists of nine sessions (3 months), structured around four main techniques, utilizing expressive tools and active/collaborative teaching-learning methodologies. Statistically significant results were observed in both self-report instruments. YSR/11-18: In the EG, there was a decrease in the total reported emotional and behavioral problems (comparison T0/T2), a reduction in thinking problems (T1), and a reduction in externalizing problems (T2); in the CG, there were no significant changes. IHSA-Del-Prette: In the EG, there was an increase in the overall repertoire of social skills (T1), a global decrease in difficulties and anxiety in social skills responses (comparison T0/T2 and T2), and significant improvements after the intervention in five out of six factors evaluated in frequency and difficulty according to the instrument; in the CG, there was an improvement in the frequency of two subscales/factors, Social Resourcefulness and Assertiveness (T1). Qualitative results supported the quantitative findings, highlighting expression and emotional regulation skills and partial inhibition of self-destructive impulses. The analyses support the hypotheses and suggest the effectiveness of the program. Conducted with the support of FUNDASP